2020
DOI: 10.1016/j.molcel.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Heterochromatin Adopts Digital Compaction States without Showing Hallmarks of HP1-Driven Liquid-Liquid Phase Separation

Abstract: Highlights d HP1 has only a weak capacity to form droplets in living cells d Size, accessibility, and compaction of heterochromatin foci are independent of HP1 d Heterochromatin compaction is ''digital'' and can toggle between two distinct states d Methodological framework to assess hallmarks of phase separation in living cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
249
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(301 citation statements)
references
References 70 publications
26
249
2
Order By: Relevance
“…It is important to note that a recent study has called into question the biological importance of the ability of HP1-a to phase-separate in vitro on its in vivo function, for example the failure of HP1-a over-expression to increase the size of heterochromatic domains as predicted for simple LLPS systems (Erdel et al, 2020). However, the complexity of feedback within heterochromatin is rife with paradox, for example the requirement for siRNA transcription to drive chromatin compaction and silencing in fission yeast (Yamanaka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that a recent study has called into question the biological importance of the ability of HP1-a to phase-separate in vitro on its in vivo function, for example the failure of HP1-a over-expression to increase the size of heterochromatic domains as predicted for simple LLPS systems (Erdel et al, 2020). However, the complexity of feedback within heterochromatin is rife with paradox, for example the requirement for siRNA transcription to drive chromatin compaction and silencing in fission yeast (Yamanaka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Swi6 recruits the H3K9me demethylase Epe1 almost exclusively into heterochromatic domains (Zofall and Grewal, 2006), which would be expected to decrease available H3K9me and thereby delocalize H3K9meengaged Swi6 molecules, likely short-circuiting the ability of elevated Swi6 levels to drive heterochromatin spreading. Moreover, the binding of HP1-/Swi6 to H3K9me and its subsequent compaction of heterochromatin involves an integrated set of activities driven by its (1) chromodomain avidity, (2) dimerization, (3) engagement of nucleosome arrays, and (4) its phase separation properties, all of which make it challenging to arrive at mechanistic conclusions without clear separation-of-function mutants or through engineered systems (Erdel et al, 2020). For this reason, the swi6-sm1 allele and others of its kind that disrupt specific functionalities will be essential in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…KMT5C, a histone H4 lysine 20 methyltransferase, shows liquid behavior within chromocenters but does not exchange with the nucleoplasm (Strickfaden et al, 2019). In contrast, CBX5, which can phase separate at high concentrations in vitro (Larson et al, 2017;Strom et al, 2017), was found to move rapidly into and out of mouse chromocenters (Erdel et al, 2020;Strom et al, 2017). We therefore performed twochannel FRAP experiments on TAMRA-dUTP labelled cells transfected with fluorescent protein tags on KMT5C or CBX5 ( Figure 2B, C).…”
Section: Replication Labeling Reveals Solid-like Behavior Of Euchromamentioning
confidence: 99%
“…However further work is needed to decipher the physical nature of these foci. Interestingly, heterochromatin foci in mouse cells were first described as liquid droplets (Strom et al 2017), but a recent study indicates that these foci rather resemble collapsed polymer globules (Erdel et al 2020). Whether specific heterochromatin factors are responsible for this collapse is not known, but HP1, the functional homolog of Sir3 does not seem required.…”
Section: Mechanisms Of Sir3 Mediated Trans-interactionsmentioning
confidence: 99%